SCHAFFER’S METHOD FOR THE TREATMENT OF AN EWE WITH UTERINE TORSION - VELLADURAI1, C; SELVARAJU, M; NAPOLEAN, R E (The Indian Journal of Animal Reproduction, 2016)
A five-year old non-descriptive full term pregnant ewe had abdominal straining and mucus discharge from the vagina since 12 h. Per vaginal examination diagnosed the ewe with right side post cervical uterine torsion that was relieved by Schaffer’s method and a live female fetus was delivered by simple traction.